The first starry night - Isom, Joan Shaddox (Dallas : Whispering Coyote Press, 1997)
Jacques encounters and befriends Vincent Van Gogh when he comes to stay in the boarding house where he works.
2.8
3-6
Keywords: Gogh, Vincent van, -- 1853-1890 -- Juvenile fiction; Gogh, Vincent van, -- 1853-1890 -- Fiction; Artists -- Fiction; France -- Fiction; Gogh, Vincent van, -- 1853-1890 -- Fiction; Artists -- Fiction; France -- Fiction